Eco-friendly cellulose based solid electrolyte with high performance and enhanced low humidity performance by hybridizing with aluminum fumarate MOF. (September 2018) - Ko, Jaeok; Kim, Seong Ku; Yoon, Yeoheung; Cho, Kyung Ho; Song, Wooseok; Kim, Tae-Ho; Myung, Sung; Lee, Sun Sook; Hwang, Young Kyu; Kim, Sang-Woo; An, Ki-Seok
Abstract: Abundant yet undeveloped, cellulose and various derivatives of cellulose are materials that we see and touch every day. Here, we report a novel polymer proton conducting electrolyte synthesized by chemical modification of hydroxypropyl cellulose, which opens a new possibility of utilizing a renowned environmental friendly material for environmentally friendly applications. The modified cellulose by attaching sulfonic acid functional groups exhibits proton conductivity of 172 mS/cm at room temperature under 100% relative humidity with negligible electron or hole leakage through the membrane. By hybridizing the modified cellulose with aluminum fumarate metal-organic-framework (A520), dehydration of the cellulose based electrolyte membrane is significantly moderated to enhance low humidity conductivity by more than an order of magnitude. The A520 hybridized sulfonated cellulose is utilized as the electrolyte for all-solid-state supercapacitor, which demonstrated specific capacitance as high as 135.14 F/g at 75% relative humidity with stable performance even at low humidity. Graphical abstract: Highlights: A novel eco-friendly polymer electrolyte is synthesized using cellulose derivative. Sulfonated cellulose exhibits high proton conductivity of 172 mS/cm at 20 °C. By adding A520 MOF, low humidity conductivity is significantly enhanced. All-solid-supercapacitor based on sulfonated cellulose-MOF electrolyte fabricated.